2020
DOI: 10.4314/ijbcs.v13i7.30
|View full text |Cite
|
Sign up to set email alerts
|

Effets du tourteau des graines de <i>Balanites aegyptiaca</i> sur la consommation alimentaire et les performances zootechniques des cabris roux de Maradi

Abstract: L’extraction d’huile contenue dans les amandes de Balanites aegyptiaca est un procédé industriel agroalimentaire qui ne cesse de se développer en Afrique sahélien mais qui génère à la fois une importante quantité de sous-produit tourteau, résultant souvent un encombrement pour les industries. Dans le cadre de la valorisation dudit sous-produit, le présent travail visait à évaluer les effets de l’incorporation du tourteau de Balanites aegyptiaca dans la ration sur les performances zootechniques des cabris roux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…These authors worked with adult castrated male Djallonke sheep kept in individual metabolic cages with an average live weight of 21.67±1.18 kg, which is heavier than the animals in the present study. However, our results corroborate those found by Akourki et al (2019) [11] who showed that goats fed a ration containing B. aegyptiaca cake consumed more feed (more than 35 g on average per animal) compared to goats in the control group. The same findings were made by Kanazoé et al (2017) [12] who also found an increase in the rate of sorghum straw intake by sheep supplemented with dried Calotropis procera leaves, in Burkina Faso.…”
Section: Discussionsupporting
confidence: 92%
“…These authors worked with adult castrated male Djallonke sheep kept in individual metabolic cages with an average live weight of 21.67±1.18 kg, which is heavier than the animals in the present study. However, our results corroborate those found by Akourki et al (2019) [11] who showed that goats fed a ration containing B. aegyptiaca cake consumed more feed (more than 35 g on average per animal) compared to goats in the control group. The same findings were made by Kanazoé et al (2017) [12] who also found an increase in the rate of sorghum straw intake by sheep supplemented with dried Calotropis procera leaves, in Burkina Faso.…”
Section: Discussionsupporting
confidence: 92%